Marital Conflict, Family Socioeconomic Status, and Depressive Symptoms in Migrant Children: A Moderating Mediational Model - Liuhua Ying; Yanli Wang; Shasha Yu (Behavioral Sciences, 2023)
The present study examines the roles of parent–child communication and peer attachment in the relationships between marital conflict, family socioeconomic status (SES), and depressive symptoms in migrant children. The present study was a cross-sectional design. A total of 437 children were selected from 2 public schools of migrant children, and they were assessed on measures of marital conflict, family SES, parent–child communication, peer attachment, and depressive symptoms. Results showed that peer attachment moderates the relationships between marital conflict, parent–child communication, and depressive symptoms. That is, for migrant children with high peer attachment, marital conflict influences depressive symptoms directly, but also indirectly through parent–child communication. For migrant children with low peer attachment, marital conflict only exerts a direct influence on depressive symptoms. In addition, parent–child communication mediates the relationship between family SES and depressive symptoms, although the mediating effects were not significant for groups with a high or a low level of peer attachment. Thus, parent–child communication serves as one critical pathway, linking marital conflict, or family SES, with depressive symptoms. Furthermore, peer attachment acts as a buffer against the negative effects of marital conflict on depressive symptoms.